VIOLATION OF THE PRINCIPLE OF MAXIM COOPERATION IN THE CONVERSATIONS BETWEEN CHARACTERS IN THE BLONDE 2022 MOVIE - Ginta Putri; Ginta Rania (ReALL - Research on Applied Linguistics and Literature, 2023)
The purpose of this research is to explain the types of violations of the principle of cooperation committed by the characters in the Blonde 2022 movie script and to describe the intention behind the violation of the principle of cooperation committed by the characters in the Blonde 2022 movie script. This research is included in the qualitative descriptive research. Furthermore, the technique used is a note-taking technique. The researcher recorded every conversation in the Blonde 2022 movie script that experienced a violation of the cooperative principle along with the implicatures that were generated based on the context of the conversation. Based on the results of research on violations of the cooperative maxim in the Blonde 2022 film script, it can be concluded that in the script there are four types of violations of the cooperative maxim committed by the characters, namely 1) violation of the maxim of quantity (1); 2) violation of the maxim of quality (1); 3) violation of relation maxim (2); and 4) violation of the maxim of manner (1). The violation that is often done is the violation of the maxim of relation by expressing utterances that are outside the context of the ongoing conversation. In the Blonde 2022 film script, there are various kinds of implicatures contained in every violation of the principle of cooperation. The implicatures contained include 1) requesting information; 2) providing information; 3) stating something (eg angry, sad, disappointed, etc.); and 4) giving orders. The most commonly found implicature is the implicature to provide information.